Reorganization of the brain and heart rhythm during autogenic meditation - Kim, Dae-Keun; Rhee, Jyoo-Hi; Kang, Seung Wan (Frontiers in Integrative Neuroscience, 2014)
The underlying changes in heart coherence that are associated with reported EEG changes in response to meditation have been explored. We measured EEG and heart rate variability (HRV) before and during autogenic meditation. Fourteen subjects participated in the study. Heart coherence scores were significantly increased during meditation compared to the baseline. We found near significant decrease in high beta absolute power, increase in alpha relative power and significant increases in lower(alpha) and higher(above beta) band coherence during 3 minute epochs of heart coherent meditation compared to 3 minute epochs of heart noncoherence at baseline. The coherence and relative power increase in alpha band and absolute power decrease in high beta band could reflect relaxation state during the heart coherent meditation. The coherence increase in the higher(above beta) band could reflect cortico-cortical local integration and thereby affect cognitive reorganization, simultaneously with relaxation. Further research is still needed for a confirmation of heart coherence as a simple window for the meditative state.